The DSM‐5 Got PTSD Right: Comment on Friedman (2013). Issue 5 (22nd October 2013) - Kilpatrick, Dean G.
<x xml:space="preserve">Abstract</x> Friedman in his article in this issue describes the posttraumatic stress disorder (PTSD) diagnosis according to the Diagnostic and Statistical Manual of Mental Disorders (5th ed.; DSM‐5) and provides considerable information about the process that resulted in the revisions, as well as how PTSD in the DSM‐5 differs from proposals for PTSD in the International Classification of Mental Disorders and Related Health Problems (ICD‐11). In this commentary, I argue that (a) the placement of PTSD in the DSM‐5 category of Trauma and Stressor‐Related Disorders is a major advance because it draws attention to the role of "nurture" when there is an overemphasis on "nature" by some; (b) the broader construct of PTSD in DSM‐5 is justified because it includes clinically important problems and can be reliably diagnosed; and (c) the web surveys contributed substantially to the provision of data needed to support proposed changes. Concerns are raised about the proposed ICD‐11 approach, and the case is presented that substantial evidence should be required before these proposed changes are made because they differ substantially from a DSM‐5 PTSD diagnosis that has demonstrated reliability and validity.